Grafting Poly(3‐hexylthiophene) from Silicon Nanocrystal Surfaces: Synthesis and Properties of a Functional Hybrid Material with Direct Interfacial Contact. Issue 26 (4th May 2016) - Islam, Muhammad Amirul; Purkait, Tapas K.; Mobarok, Md Hosnay; Hoehlein, Ignaz M. D.; Sinelnikov, Regina; Iqbal, Muhammad; Azulay, Doron; Balberg, Isaac; Millo, Oded; Rieger, Bernhard; Veinot, Jonathan G. C.
Abstract: Hybrid functional materials (HFMs) comprised of semiconductor nanoparticles and conjugated polymers offer the potential of synergetic photophysical properties. We have developed HFMs based upon silicon nanocrystals (SiNCs) and the conductive polymer poly(3‐hexylthiophene) (SiNC@P3HT) by applying surface‐initiated Kumada catalyst transfer polycondensation (SI‐KCTP). One unique characteristic of the developed SiNC@P3HT is the formation of a direct covalent bonding between SiNCs and P3HT. The presented method for obtaining direct interfacial attachment, which is not accessible using other methods, may allow for the development of materials with efficient electronic communication at the donor–acceptor interfaces. Systematic characterization provides evidence of a core–shell structure, enhanced interfacial electron and/or energy transfer between the P3HT and SiNC components, as well as formation of a type‐II heterostructure. Abstract : Hybrid functional materials of silicon nanocrystals and poly(3‐hexylthiophene) (SiNC@P3HT) consisting of a direct conjugate covalent bond between SiNC and P3HT were developed. Systematic characterization provides evidence of a core–shell structure, enhanced interfacial electron and/or energy transfer between the P3HT and SiNC components, as well as formation of a type‐II heterostructure.